Periodic Use of Gas Lift Wells in Small Mines - Turdiyev Farid Razzok ugli; Ashurov Murodullo Kholboyevich (Scientific Trends, 2024)
During the operation of piles, the formation pressure decreases. In order to maintain the flow of the well at a given level, the riser pipes are sunk deeper. In this case, the cost of the working agent will increase and the cost of extracted oil will also increase. In order to reduce the relative consumption of gas, it is advisable to periodically use low flow gas lift wells without a compressor.
Keywords: Periodic gaslift, mixture, working agent, mixing chamber, well, reverse valve, shearing tap, parafin.